Investigation of islands of resistance in complete genomes of Brucella abortus - Neto, Antonio Santiago de Sousa; Barroso, Fabricio Trindade; Dias, Cleidianne Ferreira; Veras, Adonney Allan de Oliveira; Alves, Jorianne Thyeska Castro; de Sá, Pablo Henrique Caracciolo Gomes (Seven Editora, 2024)
The current evolution of sequencing platforms has increased the amount of information generated and drastically reduced prices. The use of these technologies enabled the development of several omics sciences. Thus, conducting in silico experiments through bioinformatics provides basic information for various omics analyses, such as genomics, transcriptomics, metabolomics, among others. These analyses are especially important when the target of the study is a microorganism of biotechnological, agricultural or environmental interest, as is the case of Brucella abortus, a Gram-negative, immobile bacterium with absence of flagella, non-capsulated, non-spore-forming, aerobic, considered a facultative intracellular pathogen and whose cultivation is considered complex. Thus, the objective of this project is to analyze the complete genomes of Brucella abortus available in databases, through bioinformatics approaches, to characterize the resistance profile, evolution and mechanisms of virulence and pathogenicity. DOI:https://doi.org/10.56238/sevened2024.026-033